Comprehensive study on the administrative, economic, regional, and regulatory prospects of complementary and alternative medicine (CAM) in inflammatory bowel disease (IBD). Issue 7 (3rd July 2021) - Mousavi, Taraneh; Nikfar, Shekoufeh; Abdollahi, Mohammad
ABSTRACT: Introduction : Due to the high cost, low effectiveness, and adverse effects plus the life-long nature of inflammatory bowel disease (IBD), and misconception on safety, efficacy, and cost-effectiveness of complementary and alternative medicine (CAM), the market demand for CAM has risen over the past decades. A critical review of patients' and physicians' attitudes, market drivers, economic aspects, regulatory roles, and regional distribution is lacking. Areas covered : Through relevant databases, the existing English language literature concerning the association of CAM use with IBD was collected over the past two decades. Data was then analyzed, comprehensively summarized in tables/figures, and justified concerning administrative, organizational, regional, economic, and regulatory perspectives. Expert opinion : Although CAM utilization is more prevalent among younger, female, and high-educated IBD patients, issues concerning weak study designs, limited-time period/regional distribution of recent surveys, and lack of economic evaluations on CAM make it entirely unfeasible to draw a firm conclusion. Regulators are lagging in meeting the dire need of IBD patients, especially the elderly. Lack of legislation regarding registration, sales monitoring, licensing, insurance coverage, efficacy/safety assessments, post-marketing surveillance, quality assurance, and reference pricing alongside the limited support for CAM research are the main matters that should be urgently addressed.